Extraction of dragon fruit (hylocereus polyrhizus) foliage active compound for water treatment - Shafad, Mohd Raside (2013)
Coagulant plays a significant role in water treatment. It is used to remove the turbidity in raw water. Nowadays, natural coagulants have become interest to many researchers due to the facts that they are in abundance source, cheap, has multifunction, biodegradable and safe for human health. In this study, the potential of dragon fruit foliage (DFF) as natural coagulant was investigated. The experiments were done using standard jar test method. The coagulation process using DFF at various parameters for distilled water extraction method was done. It was found that the parameter such as drying temperature, pH, dosage, initial turbidity, and sedimentation time did have effect on coagulation process using DFF. Then, extraction of DFF active compound using different types of extraction method was carried out. It was found that the best method to extract DFF active compound was using distilled water at 60˚C where 94.4% of turbidity removal can be achieved at the dosage of 10 mg/L. Further application using surface water was found that the performance of DFF in turbidity and TSS removal was comparable with commercial alum. Lastly, the performance of DFF in coagulation process was verified using its active compound. It is believed that the main active compound of DFF is carbohydrate. The analysis for total carbohydrate content was consistent with those results obtained from jar test where extraction using distilled water at 60˚C has the highest soluble carbohydrate content and this explain why it has the highest coagulation efficiency. The result from zeta potential analysis and SEM analysis suggest that adsorption and interparticle bridging mechanism is the main mechanism of DFF in coagulation process. As a conclusion, DFF has a bright future and good potential for application in water treatment.